A study on perception of investors of Amanah Saham Nasional Berhad (ASNB) Shah Alam branch towards the quality services of agents/ Masrul Hayati Kamarulzaman - Kamarulzaman, Masrul Hayati (Faculty of Business and Management, 2010)
This study is to investigate the perception of investors toward the quality services of agents. This study has been done at Amanah Saham Nasional Berhad (ASNB) Shah Alam branch. ASNB have appoint and make an agreement with Maybank, CIMB,RHB and Pos Malaysia as a agents to carry the wide range of services and products of ASNB to the investors. So, the first objective of this study is to study the perception of investors of Amanah Saham Nasional Berhad (ASNB) Shah Alam branch toward the quality services of agent. The second objective is to determine the relationship between independent and dependent variables which are service environment, interaction quality, reliability and empathy and to determine the most influence dimension toward the investors perception of agents’ service quality . Descriptive research has been chosen as a research design and the method for data collection for this study is questionnaire. 200 questionnaires have been personally distributed to the investors at Amanah Saham Nasional Berhad Shah Alam who are currently or previously had done the transaction with the agents. The distribution process was taken all the operation hours which is from 8.15 a.m until 4.00p.m and from 4th October until 15th October 2010. The analysis of findings in this study consists of frequencies of demographic profile, crosstabulation analysis, Reliability analysis, Pearson correlation and Multiple Linear Regression. Lastly is the conclusion and recommendation, researcher will determine which dimension that most contribute to the investor perception and the relationship between service quality dimensions and investor perception. The researcher will make the recommendations in this study based on the conclusion and observations